2014
DOI: 10.1155/2014/417603
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification Surgery in Eyes with Neovascular Age-Related Macular Degeneration

Abstract: Purpose. To evaluate the visual outcomes and effect of phacoemulsification surgery on the progression of neovascular age-related macular degeneration (AMD). Methods. Retrospective, noncomparative, and interventional case series. Thirty eyes from 29 subjects with neovascular AMD treated with intravitreal antivascular endothelial growth factor (VEGF) injections who underwent phacoemulsification and had a postsurgery follow-up of 6 months were included. LogMAR best corrected visual acuity (BCVA) was assessed preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…It is known that neovascular AMD, can compromise in 90% of cases severely the vision (20/200 or worse) if left untreated [37], but with the advent of anti-vascular Endothelial Growth Factor (anti-VEGF) intravitreal injections as therapy in wet AMD has got stabilize (90%) or even improved vision (30%) in a large number of cases [38][39][40][41][42][43].…”
Section: Neovascular Amdmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that neovascular AMD, can compromise in 90% of cases severely the vision (20/200 or worse) if left untreated [37], but with the advent of anti-vascular Endothelial Growth Factor (anti-VEGF) intravitreal injections as therapy in wet AMD has got stabilize (90%) or even improved vision (30%) in a large number of cases [38][39][40][41][42][43].…”
Section: Neovascular Amdmentioning
confidence: 99%
“…More recently, studies published have not showed an increase in recurrence, number of injections or worsening of visual acuity when compared with non-operated eyes [15,16,[25][26][27][39][40][41][42][43][50][51][52][53][54][55][56]. However, Lee and cols.…”
Section: Neovascular Amdmentioning
confidence: 99%
See 2 more Smart Citations
“…47 The most recent study published by Grixti et al on 30 eyes from 29 subjects with nAMD actively treated by anti-VEGF who underwent phacoemulsification demonstrated a gain in vision from 0.69 LogMAR preoperatively to 0.6 at final visit (p = 0.0011) and no increased need for injections over the time of follow-up (average 0.167/month) at six-month follow-up. 48 The authors were encouraged by the findings and advocated for future larger prospective studies with more stringent monitoring mechanisms using formal fluorescein angiography and optical coherence tomography imaging to monitor disease progression following cataract extraction.…”
Section: Case Seriesmentioning
confidence: 99%